Heat-treated NiTi instruments and final irrigation protocols for biomechanical preparation of flattened canals - Kleber Kildare Teodoro CARVALHO; Igor Bassi Ferreira PETEAN; Alice Corrêa SILVA-SOUSA; Rafael Verardino CAMARGO; Jardel Francisco MAZZI-CHAVES; Yara Terezinha Corrêa SILVA-SOUSA; Manoel Damião SOUSA-NETO (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study evaluate shaping ability of heat-treated NiTi-alloy instruments associated with different final irrigation protocols in flattened root canals. Thirty human mandibular incisors with flattened root canals were divided into 5 groups (n = 10): (XP) Original Protocol XP-endo Shaper; (XP-WT) Original Protocol XP-endo Shaper with working time variation; (XP-K) XP-endo Shaper with kinematics variation; (XP-WTK) XP-endo Shaper with kinematics and working time variations; (Hyflex) Hyflex CM. For the variation in working time protocols the same sample of the XP-endo Shaper groups with and without kinematic variation were used. To evaluate final irrigation protocols, groups 1, 3 and 5 were submitted to 3 protocols: (NI) No irrigation (n = 2); (CI) conventional irrigation (n = 4), and (EndoVac) irrigation (n = 4). The samples were scanned by microcomputed tomography and prepared for scanning electron microscopy evaluation. Quantitative data were evaluated using the parametric ANOVA test, with statistical significance level set at 5%, and qualitative data obtained were compared to establish the agreement between examiners through the Kappa test. It was observed that in the analysis of XP-endo Shaper protocols, the additional working time did not cause difference in any of parameters evaluated (p > 0.05) in relation to time recommended by manufacturer. Compared to Hyflex, XP-K showed highest mean volume increase (p < 0.05) and lowest percentage of untouched walls (p < 0.05). In the qualitative evaluation, final irrigation protocol with EndoVac provided the best cleaning results when associated with XP-K and with Hyflex. Thus, supplementary techniques are effective tools to enhance cleaning and to promote higher touch of walls during root canal preparation.